The Seasonal Variations in Fouling Organisms and Their Relationship with Environmental Factors on a Raft Culture Facility in Pastoral Marine Ranching - Peiqi YANG; Yanli TANG; Mengjie YU; Hui LIANG (Progress in Fishery Sciences)
Marine ranching is a fishery model that can improve the ecological environment of sea areas, increase and conserve fishery resources, and realize the sustainable utilization of fishery resources. It is widely used worldwide. In Shandong Province, marine ranching is divided into the following types: Reef casting, game fishing, bottom seeding, pastoral, and equipment, based on the production mode. Among them, pastoral marine ranching refers to marine ranching dominated by three-dimensional ecological aspects such as raft culture facilities.Raft culture facilities are a culture framework that must be constructed for the culture of bivalves such as oysters, scallops, and mussels in China's coastal waters. These facilities include six parts: a wooden pile, pursed rope, float, suspended cage, suspended rope, and floating rope. In the process of bivalve culture, the construction of a raft culture facility provides a good adhesion substrate for other organisms in the ocean, and a large number of fouling organisms will inhabit and survive on the culture facility. The activity of these fouling organisms will soften the raft culture facility and shorten the service life of the raft culture facility. Furthermore, the fouling organisms can plug the mesh, leading to the death of the farmed shellfish due to lack of oxygen, causing economic losses. However, relevant studies have also shown that the presence of fouling organisms can accelerate the rate of nutrient salt exchange between suspended organisms and aquaculture waters, which can promote the growth of phytoplankton, improve primary productivity, provide more bait for bivalve culture, and increase the fertility of bivalve culture, which is beneficial to bivalve culture. There are differences in the relationship between the fouling organisms' species number and biomass and environmental factors across different raft aquaculture areas. Therefore, basic research must be conducted on fouling organisms in raft culture areas to provide reference for healthy bivalve culture and further provide basic data for exploring the impact of fouling organisms on the ecological environment in raft culture facilities.To explore the seasonal changes of fouling organisms in raft culture facilities of pastoral marine ranching and their relationship with environmental factors, a 4-quarter survey was performed in the pastoral marine ranching area of Rushan Huaxin Foodstuffs Co., Ltd., from July 2022 to April 2023. A total of four fixed stations were set up in the raft culture area of oysters for each survey. The fouling organisms were investigated at each station. An area of 10 cm × 10 cm in the float, a length of 30 cm of the floating rope, and an area of 20 cm × 20 cm in the suspended cage were sampled. The collected samples were bottled and numbered; then, the sample was fixed and stored in 5% formaldehyde solution, and returned to the laboratory for species identification and counting. The species, biomass, diversity, dominant species, and community structure of the fouling organisms at three different sampling sites were analyzed, and the relationship between environmental factors and dominant species was determined by redundancy analysis (RDA) and Spearman analysis.The results showed that 35 species of fouling organisms were found in eight categories, including 13 species of Crustacea, 8 species of Mollusca, 4 species of Polychaeta, 3 species of Chordate, 2 species of Cnidaria and Phaeophyta, and 1 species each of Rhodophyta, Chlorophycophyta, and Echinodermata. There were significant seasonal variations in the community structure of fouling organisms. Furthermore, there were significant differences in the community structures of fouling organisms in suspended cages, floating ropes, and floats, and the biomass varied in the ranges of 31.48~1 645.82 g/m2, 23.22~580.76 g/m2, and 5.76~30.12 g/m2, respectively. The maximum biomass of fouling organisms appeared in summer. The richness index, evenness index, and diversity index of the fouling organisms ranged from 1.38 to 3.61, 0.33 to 0.92, and 0.88 to 2.58, respectively. The lowest richness index was observed on the summer float, the lowest evenness index and diversity index were observed on the summer suspended cage, and the three indexes reached the highest values on the spring suspended cage. The dominant species of fouling organisms belonged to the phyla Crustacea and Mollusca. Mytilus edulis was the dominant species on the floating ropes and suspended cages, and Caprella aino was the dominant species on the floats. The dominant species of fouling organisms in the float showed obvious seasonal changes. The dominant species on the float in summer was Perinereis aibuhitensis, and that in autumn was Crassostrea gigas. Gracilaria vermiculophylla was the dominant species on the float in winter and spring. The RDA results of dominant species and environmental factors showed that transparency, temperature, silicate levels, and chlorophyll were the main environmental factors affecting the community structure of fouling organisms, and the correlation between different species and environmental factors was also different. In this study, the seasonal variation of fouling organisms and their relationship with environmental factors were investigated in the Rushan oyster raft culture facility, and our results can provide reference for healthy oyster culture in this area.